The Effect of Financial Performance and Firm Size on Stock Return in Miscellaneous Industrial Sector on the Indonesia Stock Exchange (Universitas Dr. Soetomo, 2022)
The purpose of this study is to analyze the effect of profitability, liquidity, leverage, and firm size on stock returns of Miscellaneous industrial sectors on the Indonesia Stock Exchange. The sample consist of 17 companies, which are taken by purposive sampling technique. The analysis technique used is multiple linear regression. The results of this study indicate that simultaneously the variables of profitability, liquidity, leverage, and firm size have a significant effect on the stock return. Partially, profitability has a significant positive effect and liquidity has a significant negative effect on stock returns. Meanwhile, leverage and firm size partially have no effect on stock returns. The results showed that stock returns will increase with increasing profitability and low liquidity. Increased profitability of the company will increase profits that can be distributed to shareholders. The company's profitability can increase with low liquidity as long as its current assets can meet its current liabilities. This condition is attractive to investors so that the company's stock price increases as well as its stock return